Sie sind auf Seite 1von 12

ENGR 012 Slide 1

Examples of Convolution
There s no need to fear,
Theres
fear
convolution is here!

Review
Impulse response: h(t)
Input: x(t)
Output: y(t)

y(t)) = h(t)
y(
( ) x(t)
( ) = x(t)
( ) h(t)
()
=

h()x(t )d = x()h(t )d

Given the impulse response of a system, and the input to the system,
we can find the output by using convolution.

ENGR 012 Slide 2

Example Systems

System 1:
M
Mass
with
ith sliding
lidi
ffriction,
i ti
input=fa(t), output=v(t)
M=1, b=2;

Step response of mass-friction system

Impulse response of mass-friction system

0.8

0.8

ht=yy (t)

y (t)

0.6
0.4

0.6
0.4

0.2

0.2

-1

1
Time (seconds

-1

b
t
1
1
M
y 1(t) = 1 e (t) =
1 e2t (t)
b
2

1
Time (seconds

1 Mb t
h1(t) = e (t) = e2t (t)
M

Step response of spring-friction


spring friction system

I
Impulse
l response off spring-friction
i f i ti system
t

0.8

0.5

h(t))=y (t)

0.6

y (t)

System 2:
Spring and friction in parallel,
input=fa(t), output= v(t)
k=1, b=2

0.4
0.2

0
-0.5

0
0

y 2(t) =

1
e
k

4
6
Time (seconds

k
t
b

(t) = e

(t)

10

-1
0

4
6
Time (seconds

10

1
1 kb t
h2 (t) = (t) e (t)
k
b
1 t
= (t) e 2 (t)
2

ENGR 012 Slide 3

Example 1 / System 1
What is step response of h1(t)?
+

y(t) = h1(t) * x(t) =

h ()x(t )d = x()h (t )d
1

{e

y(t) =

() {(t )} d =

2(t )

(t)
e
(t )} d
{
}
{

Change
g lower limit of integration:
g
()=0,
(
) , <0
+

y(t) =

Step
p response
p
of mass-friction system
y
1

(t )d

0.8
0.6

y (t)

Change upper limit of integration:


(t-)=0, t-<0; or (t-)=0, >t
t

y(t) = e

y(t) =
y(t) =

1
d = e2
2

1
1 e2t (t)
2

0.2
0
-1

t
0

1 2t
1
e 1 =
1 e2t ,
2
2

0.4

t>0

(functional form)

1
Time (seconds

Note 1: we get both the homogeneous and


the particular solution but can only solve
problems with zero initial conditions.
Note 2: this was a p
pointless exercise. We
used the impulse response to find the step
response but we needed to use the step
response to find the impulse response in the
first place (previous slide). Soon we will be
able to find the impulse response directly.

Example 2 / System 1

ENGR 012 Slide 4

What is ramp response of h1(t) (i


(i.e.,
e x(t)=t(t))?
2 ( t )

)
e
(t )} d
{
}
{

y(t) =

x()h1(t )d =

y(t) =

2 ( t )

d =

2t

e d = e

2t

y(t) = e2t

1 e2 = e2t
2 (2 )2

t 1 2t 1
e
4
2 4

1 2t
1
2 t
2
y(t) = e2t

e
+

4
2 4

t 1 1 2t
+ e
2 4 4
1
1

= t 1 e2t ,
2
2

Ramp response of mass-friction


mass friction system
4
input
output
3

t>0

y ramp(t)

y(t) =

or

t 1 1

y(t) = + e2t (t)


2 4 4

0
-1

2
Time (seconds

ENGR 012 Slide 5

Example 3 / System 2

What is step response of h2(t)?


+

y(t) =

x()h (t )d
2

1 2 (t )
y(t) = () (t ) e
(t ) d
2

(t )
1
y(t) = ()(t )d ()e 2
(t )d
2

sifting property
1 +

1 t

1 t
1 t
y(t) = (t) e 2 ()e 2 (t )d = (t) e 2 e 2 d
2
2

0
t

1
1
1
1
t

t
1
2
2
2
= (t) e e2 1
y(t) = (t) 2 e e
2

Step response of spring-friction system


1

0.6

t>0

0.8
y (t)

1
1
t
t

y(t) = (t) 1 e 2 = e 2 ,

04
0.4
0.2

y(t) = e

1
t
2

(t)

0
0

4
6
Time (seconds

10

ENGR 012 Slide 6

Example 4 / Graphical Convolution (1)


What is convolution of g(t)=0
g(t)=0.5e
5e-t(t) with f(t)=2((t)
(t)- (t
(t-3))?
3))?
+

y(t) = g(t) f(t) =

f()g(t )d

We could do it mathematically,
y, but it is useful to visualize the process.
p
2s(t) & 2s(t-3) vs t

f(t) vs t
2

f() vs

2s(t)
2s(t-3)

f()

1.5

f(t)

0.5
0
-2

2
t (seconds

0
-2

time reversal
because of -

g() vs

2
t (seconds
(
d

0
-2

2
(seconds

shift by t
g(-) vs

g(t-) vs , for t=1


2

0
-2

(
d
(seconds

2
g(-)

0
-2

g(t-)

2 (t) and 2 ((t-3)

g()

change of variable
from t to

2
(seconds

0
-2

(seconds

So the convolution process is: flip, shift (for each value of t), multiply, integrate (fsmi).

ENGR 012 Slide 7

Example 4 / Graphical Convolution (2)


+

y(t) = g(t) f(t) =

f(), g(t-), and their product vs , for t=-1

f()g(t )d

f()

g(t) = 0.5e t (t)


f(t) = 2((t) (t 3))

g(t-)
product

1.5

0.5

Because one of the inputs is


described piecewise, split
convolution integral into
pieces.

0
-2

-1

2
(seconds

y(t), t<0

Consider, first, t<0 (Region 1).

fsmi
Since the product is always 0,
g
is zero.
the integral

y(t)

1.5

0.5

y(t) = 0,

t<0

0
-2

-1

2
t (seconds

ENGR 012 Slide 8

Example 4 / Graphical Convolution (3)


+

y(t) = g(t) f(t) =

f()g(t )d

f(), g(t-), and their product vs , for t=1.5

f()

g(t) = 0.5e (t)


f(t) = 2((t) (t 3))

g(t-)
product

15
1.5

Now consider 0<t<3 (Region 2).


2)

0.5

fsmi

-2

y(t) = 0.5 2e
y(t) = e

e d = e

2
(seconds

y(t), 0<t<3

y(t) = e t (et e0 ) = e t (et 1)


y(t)
(t) = (1 e t )),

d = e ted

(t )

0<t<3

1.5
y(t)

-1

0.5

0
-2

-1

2
t (seconds

ENGR 012 Slide 9

Example 4 / Graphical Convolution (4)


f(),
) g(t
g(t-),
) and their product vs , for t=4

f()g(t )d

y(t) = g(t) f(t) =

f()

g(t) = e t (t)
f(t) = 2((t) (t 3))

1.5

Now consider 3<t (Region 3).

0.5

y(t) = 0.5 2e
y(t) = e

e d

-2

-1

d = e e d

(t )

=e e

value at t=3

3<t

y(t), 3<t

1.5

y(t)
(t) = e t ((e3 e0 ) = e t (e
( 3 1)
y(t) = (e3 t e t ),

(seconds

y(t))

fsmi

g(t-)
product

0.5

homogeneous
response decay
(delayed 3 sec)

y(t) = (e(t 3) e t ) = (1 e3 )e(t 3)

0
-2

-1

2
t (seconds

Understanding of this form of equation is not crucial.

ENGR 012 Slide 10

Example 5 / Graphical Convolution (1)


f(t) vs t

What is y(t)=f(t)*g(t)

2.5
2

f(t)=2((t)- (t-1))
f(t)

1.5

g(t)=((t)- (t-2))/2

1
0.5
0
-0.5
-3
3

-2
2

-1
1

1
2
t (seconds

g(t) vs t
2.5
2

g(t)

1.5
1
0.5
0
-0.5
-3

-2

-1

1
2
t (seconds

This time we will need to split up the integral into five regions

ENGR 012 Slide 11

Example 5 / Graphical Convolution (2)


f(()), g(tg( ) and product
p
for t=-.5, ((Region
g
1))

Region 1: (t<0)

f()

g(t-)

f()g(t-)

0
-3

-2

-1

1
2
(seconds)

f(), g(t-) and product for t=0.25, (Region 2)

0
t

0
-2
2

-1
1

1
2
(seconds)

f(t) g(t) = f()g(t )d


0

0
-3

-2

-1

1
2
(seconds)

f(t) g(t) = f()g(t )d

0
-2

-1

1
2
(seconds)

f(), g(t-) and product for t=5, (Region 4)

1
(2) 2 d = 3 t

t 2

f(t) g(t) = f()g(t )d

0
-3

(2) 2 d = 1
0

f(), g(t-) and product for t=2.5, (Region 4)

-3

(2) 2 d = t
0

Region 5: (3<t)

= 0 = 0

f(t) g(t) = f()g(t )d

f(), g(t-) and product for t=1.33, (Region 3)

Region 4: (2<t<3)

1
-3
3

Region
g
3: ((1<t<2))

f(t) g(t) = f()g(t )d

Region 2: (0<t<1)

-2

-1

1
2
(seconds)

= 0 = 0
0

ENGR 012 Slide 12

Example 5 / Graphical Convolution (3)


f(t) vs t

f(t)

0
-3

-2

-1

1
2
t (seconds)
g(t) vs t

-2

-1

2
t
y(t)=f(t)*g(t)

-2

-1

1
2
t (seconds)

g(t)

1
0
-3

y(t)

1
0
-3